Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Evolution of the Antarctic Ice Sheet Over the Next Three Centuries From an ISMIP6 Model Ensemble - Seroussi, Hélène; Pelle, Tyler; Lipscomb, William H.; Abe-Ouchi, Ayako; Albrecht, Torsten; Alvarez-Solas, Jorge; Asay-Davis, Xylar; Barre, Jean-Baptiste; Berends, Constantijn J.; Bernales, Jorge; Blasco, Javier; Caillet, Justine; et al. (Earth's Future, 2024)
Abstract The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) is the primary effort of CMIP6 (Coupled Model Intercomparison Project?Phase 6) focusing on ice sheets, designed to provide an ensemble of process-based projections of the ice-sheet contribution to sea-level rise over the twenty-first century. However, the behavior of the Antarctic Ice Sheet beyond 2100 remains largely unknown: several instability mechanisms can develop on longer time scales, potentially destabilizing large parts of Antarctica. Projections of Antarctic Ice Sheet evolution until 2300 are presented here, using an ensemble of 16 ice-flow models and forcing from global climate models. Under high-emission scenarios, the Antarctic sea-level contribution is limited to less than 30 cm sea-level equivalent (SLE) by 2100, but increases rapidly thereafter to reach up to 4.4 m SLE by 2300. Simulations including ice-shelf collapse lead to an additional 1.1 m SLE on average by 2300, and can reach 6.9 m SLE. Widespread retreat is observed on that timescale in most West Antarctic basins, leading to a collapse of large sectors of West Antarctica by 2300 in 30%?40% of the ensemble. While the onset date of retreat varies among ice models, the rate of upstream propagation is highly consistent once retreat begins. Calculations of sea-level contribution including water density corrections lead to an additional ?10% sea level and up to 50% for contributions accounting for bedrock uplift in response to ice loading. Overall, these results highlight large sea-level contributions from Antarctica and suggest that the choice of ice sheet model remains the leading source of uncertainty in multi-century projections.
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; klimamodeller

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting